Persistent Behavior in Energetic Neutral Atom Time Series from IBEX - N. V. Sarlis; G. Livadiotis; D. J. McComas; M. Alimaganbetov; N. A. Schwadron; K. Fairchild (The Astrophysical Journal)
We investigate the long-term persistence of the time series of energetic neutral atom (ENA) fluxes recorded by the Interstellar Boundary Explorer (IBEX). ENAs provide global information about the outer heliosphere and its interactions with the very local interstellar medium. To avoid the IBEX Ribbon, here, we focus our analysis solely on the polar regions N60°–N90° and S60°–S90°. Each year, IBEX takes two measurements of every pixel in the sky. We make use of the whole set of 14 yr of IBEX data and adhere to the correct time order for the construction of the flux time series. We examine in detail both the trend and the fluctuations of these time series. Using modern methods of time series analysis and persistence characterization, we show that the time series (i) trend is influenced by the solar cycle, (ii) persistence can be established independently of the presence of this trend, and (iii) statistical properties of the fluctuations differs between north and south, pointing to the existence of anisotropy and thus a north–south asymmetry.